Teaching or Manipulating? On the Adoption of Bright and Deceptive Patterns by Duolingo - Castro, João Vítor; Valença, George (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2025)
Introduction: In 2024, Duolingo surpassed 100 million active users, including a large number of children, raising concerns about its design practices. Objective: This study aims to critically examine Duolingo’s interface through the lens of fair and deceptive design patterns, especially regarding children’s rights. Methodology or Steps: We conducted a qualitative analysis of the platform’s visual and interaction elements, focusing on engagement strategies. Expected Results: While Duolingo employs ethical practices like clear interfaces, we identified manipulative patterns such as excessive notifications and emotionally charged visuals. These findings contribute to discussions on ethical design in educational apps for children.